Generalization of the Transformation Method to the Stratonovich Formula for Solving Stochastic Differential Equations - Ali alojedi; Abdulghafoor J. Salim (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this research, the reducible method or what is called the transformation method was generalized to the Stratonovich formula used to solve stochastic differential equations (SDEs), and the general formulas for the solutions and their theories were reached and the conditions necessary for reducing the stochastic differential equation were clarified by generalizing this method from the Ito integration formula to the Stratonovich integration formula and the transformation method between them, and these two integration formulas (Ito formula and Stratonovich formula) were applied to a group of diverse examples and the solutions were obtained and drawn (by the MATLAB program) and the results of the solutions for both methods were compared.